When will it snow? - Crisp, Marty; Eisner, Viv, 1957- (New York : Scholastic, 2002)
In the middle of June, Peter, "a boy of winter who's stranded in summer," is longing for snowy days.
"Originally published as Totally polar."
"This edition is only available for distribution through the school market"--P. [4] of cover.
Keywords: Snow -- Juvenile fiction; Winter -- Juvenile fiction; Humorous stories; Stories in rhyme -- Juvenile fiction